2007
DOI: 10.2116/analsci.23.85
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Selective Sensing of Cysteine Using Gold Nanoparticles Conjugated with a Thermoresponsive Copolymer Having Carboxyl Groups

Abstract: We describe a simple, yet selective cysteine sensor based on gold nanoparticles (AuNPs) conjugated with thermoresponsive copolymers, the carboxyl groups of which are incorporated. Copolymer-conjugated AuNPs, used as the cysteine sensor, in a solution form sediment when cysteine is added. Heating followed by cooling the solution induces phase transitions of the thermoresponsive copolymers, resulting in an acceleration of sedimentation of the copolymer-conjugated AuNPs. The absorbance of supernatants at 520 nm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The addition of glutathione results in spontaneous disassembly of the aggregates with a concomitant colorimetric response. AuNPs conjugated with thermoresponsive copolymers have also been utilized for the colorimetric sensing of thiol compounds [254,255].…”
Section: Sensing Small Organic Moleculesmentioning
confidence: 99%
“…The addition of glutathione results in spontaneous disassembly of the aggregates with a concomitant colorimetric response. AuNPs conjugated with thermoresponsive copolymers have also been utilized for the colorimetric sensing of thiol compounds [254,255].…”
Section: Sensing Small Organic Moleculesmentioning
confidence: 99%
“…The other thermoresponsive copolymers, poly(N-isopropylacrylamide(90 mol%)-co-N-acryloyltryethylenetetramine (10 mol%)) (p(NIP0.9-TETA0.1)), poly(N-isopropylacrylamide (90 mol%)-co-N-methacrylate(10 mol%)) (p(NIP0.9-MA0.1)) 24 and poly(N-isopropylacrylamide) (pNIP), 3 were synthesized with corresponding monomers by radical polymerization, as reported elsewhere.…”
Section: Preparation Of Thermoresponsive Copolymermentioning
confidence: 99%
“…Colorimetric sensing systems have been fabricated based on colorimetric properties that can be controlled externally using thermoresponsive gold nanocomposites. [23][24][25][26] Considering these previous applications based on the versatile properties, thermoresponsive gold nanocomposites also have the potential for use as drug delivery materials and nano-actuators. In this study, we investigated the conjugation of gold nanoparticles with thermoresponsive polymers for fabricating thermoresponsive gold nanocomposites as a model of drug delivery materials and colloidal sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the result suggested a detection limit as low as 100 nM, which is much lower than those of other AuNPs-based spectrophotometric methods. [20][21][22] To investigate the selectivity for cysteine detection with the proposed method, we also measured the influences of the other 19 essential amino acids according to the proposed analytical procedure. Figure 3B showed that the A600nm/A520nm value of cysteine was strikingly larger than those of the other 19 amino acids, indicating that the assay approach has very high specificity towards cysteine among the 20 essential amino acids.…”
Section: Sensitivity and Selectivitymentioning
confidence: 99%
“…Okubo et al constructed a cysteine sensor based on 13 nm diameter citrate-capped AuNPs conjugated with thermoresponsive copolymers, the carboxyl groups of which were incorporated. 21 The cysteine concentration could be obtained by a sigmoidal profile at a concentration range between 1 to 6 µM. Wu et al developed a sensor for detecting cysteine in a solution of 13 nm diameter fluorosurfactant-capped AuNPs.…”
mentioning
confidence: 99%